Biestabilidade óptica em átomos de três níveis em uma cavidade óptica - Proença, Lucas Araujo (Universidade Federal de São Carlos, 2023)
The phenomenon of optical bistability in atomic systems confined in an optical cavity has been extensively explored due to its potential for applications such as optical switches, memories and optical transistors. The bistability observed in multi-level atomic systems has some advantages over the usual two-level system with respect to non-linear optical properties, absorption and scattering. The configuration of atoms with more than two levels allows the use of other electromagnetic fields by coupling different atomic transitions resonantly, or quasi-resonantly, making it more feasible to manipulate and control non-linear optical processes, which may be related to the phenomena of electromagnetically induced transparency (EIT - \textit{Electromagnetically Induced Transparency}) and coherent population trapping (CPT - \textit{Coherent Population Trapping}). In this work we theoretically study the CPT phenomenon in cavities to explore the control and properties of optical bistability in systems composed of $N$ three-level atoms in $\Lambda$ configuration, independently coupled to the same field mode of an optical cavity. To obtain the interaction hamiltonian of the system we used the semiclassical approximation, which consists of considering atoms quantumly and the cavity field classically. Through the formalism of the master equation, we derive the Maxwell-Bloch equations and the dynamics of the system was obtained through computational simulations performed in MATLAB. The obtained results show that it is possible to obtain a sensitive control of the optical bistability from the adjustment of parameters external to the system, such as the frequency and intensity of the test field and the intensity of the control field. The possibility of controlling light with observed light in the studied system, through the phenomenon of optical bistability, can be promising for the development of optical devices with different functionalities.
Optical bistability of three-level atoms in an optical cavity
Keywords: Biestabilidade óptica; Eletrodinâmica quântica em cavidades; Aproximação semiclássica; Aprisionamento coerente de população em cavidades; Optical bistability; Cavity quantum electrodynamics; Semiclassical approximation; Cavity coherent population trapping; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA ATOMICA E MOLECULAR::ESPECTROS ATOMICOS E INTEGRACAO DE FOTONS